Respostas

2014-05-19T21:57:12-03:00
√3x(√18+32)-√188÷√19=
√3x(√3².2+√2².2².2)-√2².47÷√19=
√3x(3√2+4√2)-2√47÷√19=
√3x(7√2)-2√47÷√19=
7√6-2√47÷√19=
√7².6-√2².47÷√19=
√294-√188÷√19=
106÷19=
5,47

18|2             32|2                        188|2                    19|19
9|3               16|2                          94|2                     1
3|3                8|2                           47|47
1  3².2           4|2                              1    2².47
                    2|2
                    1    2².2².2